Chemo-enzymatic production of omega-3 monoacylglycerides using sponge-like ionic liquids and supercritical carbon dioxide. Issue 17 (11th August 2020) - Villa, Rocio; Alvarez, Elena; Nieto, Susana; Donaire, Antonio; Garcia-Verdugo, Eduardo; Luis, Santiago V.; Lozano, Pedro
Abstract : Chemo-enzymatic synthesis of omega-3 monoacylglycerides was carried out in two steps, the enzymatic transesterification of fish or linseed oil with solketal, followed by the hydrolysis of solketal moieties catalysed by acid zeolites in either scCO2 or sponge-like ILs. Abstract : A clean chemo-enzymatic synthesis of omega-3 monoacylglycerides was carried out in two consecutive catalytic steps, the enzymatic transesterification of raw fish or linseed oil with solketal for producing fatty acid solketal esters, followed by the hydrolysis of these solketal moieties catalysed by solid acids ( e.g. zeolites) in either supercritical carbon dioxide (scCO2 ) or sponge-like ionic liquids (SLILs). By using scCO2 as the reaction/extraction medium, an excellent performance of both coupled catalytic steps was observed when t -butanol was used as a co-solvent, resulting in 100% monoacylglyceride yield in seven days under continuous operation and without any loss in catalytic activity. For discontinuous operation, the process involved two separate steps in SLIL and water, respectively, leading to 100% product yield and an IL-free monoacylglyceride product by following a cooling and centrifugation protocol, which allows for the full recovery of the enzyme/SLIL/zeolite components of the reaction system that could be reused for at least 6 cycles with unchanged catalytic performance.